In vitro antiviral activity of Coriandrum sativum L. seed crude extracts against Respiratory Syncytial Virus - Ramasamy, Darssheela; Ashaari, Nur Suhanawati; Balia Yusof, Zetty Norhana; Abdul Wahab, Azimah; Zakaria, Iffah Izzati; Ismail, Saila (University of Malaya, 2025)
Human respiratory syncytial virus (RSV) causes severe lower respiratory infections in young children and the elderly. Currently, no specific antiviral drug exists for RSV. Ribavirin, a broad-spectrum nucleoside analogue originally used for hepatitis C virus, is reserved for severe RSV cases because of its side effects and high cost. This underscores the need for safer, more affordable alternatives. Coriandrum sativum L. (coriander) has shown antiviral activity against several viruses; however, its potential against RSV remains unexplored. This study investigates the antiviral effects of coriander seed extracts against RSV in vitro. Methanolic (MSECS), hexane (HSECS), and aqueous (ASECS) extracts of coriander seeds were tested on RSV-infected BEAS-2B human bronchial epithelial cells. Intracellular viral loads were quantified using end-point PCR, and extracellular infectious titres were assessed via 50% tissue culture infectious dose (TCID50) assay. Gas chromatography-mass spectrometry (GC-MS) was used to identify bioactive compounds in the extracts. At non-toxic concentrations of 62.5 and 125 µg/mL, MSECS, HSECS, and ASECS significantly reduced RSV intracellular RSV loads, comparable to ribavirin control. At 125 µg/mL, MSECS, HSECS, and ASECS decreased extracellular viral titres by 97%, 84%, and 98%, respectively, surpassing ribavirin’s inhibitory effect. GC-MS analysis revealed hexadecanoic acid, octadecanoic acid, linalool, and myristic acid as common major compounds across all extracts. Additionally, MSECS contained geranyl acetate (7.57%), HSECS included capric acid (25.1%), and ASECS was rich in cis-vaccenic acid (60.7%). Some of these compounds are known for their antiviral properties, suggesting a potential synergistic mechanism in RSV inhibition. Our results provide the first evidence that Coriandrum sativum L. crude extracts possess potent in vitro antiviral activity against RSV and may serve as novel, safe, and affordable antiviral agents against RSV.